2003
DOI: 10.1183/09031936.03.00018202
|View full text |Cite
|
Sign up to set email alerts
|

A cyclosporin A/maltosyl- -cyclodextrin complex for inhalation therapy of asthma

Abstract: The inhalation of cyclosporin (Cs)A to the lung is limited by its hydrophobic properties. In order to improve the poor solubility of CsA, cyclodextrin (CD) was evaluated for its suitability for dry powder inhaler formation, and the benefit of an inhaled CsA/CD complex in vivo was demonstrated.The solubilising effect of CDs on CsA was measured by high-performance liquid chromatography. Ciliostatic activity and haemolysis were determined to assess some safety profiles of CDs. The efficacy of an inhaled CsA/CD co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In these studies, no data are available on the potential lung toxicity of CD [8]. A very recent study showed that cyclosporin A-maltosyl-α-CD complexes were useful as therapy for allergen-induced inflammation with an apparently low toxicity [7]. Using high doses of intravenously administered HP-γ-CDs (> 600 mg/kg), the occurrence of a pulmonary accumulation of macrophages (histiocytosis) was demonstrated [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, no data are available on the potential lung toxicity of CD [8]. A very recent study showed that cyclosporin A-maltosyl-α-CD complexes were useful as therapy for allergen-induced inflammation with an apparently low toxicity [7]. Using high doses of intravenously administered HP-γ-CDs (> 600 mg/kg), the occurrence of a pulmonary accumulation of macrophages (histiocytosis) was demonstrated [20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the outer, hydrophilic region of the CD induces solubilization through interaction with water molecules [4]. Little has yet been published concerning the pulmonary applications of cyclodextrins [5][6][7][8]. It was found that hydrophilic cyclodextrin derivatives could be used in liquid formulation to be administered by inhalation thus increasing drugs solubility, but very little data was given as to the potential toxicity of CD formulations on the lung parenchyma and bronchial tree.…”
Section: Introductionmentioning
confidence: 99%
“…CTS (relative molecular mass 7 1.1 10 × , deacetylation degree 80%) was prepared in our laboratory by the method of acetic acid hydrolyzes referenced from Chen et al [12] . All other chemicals and reagents used were of analytical grade and provided by Shanghai Chemical Reagent Company (USA).…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [6] have prepared a new theophylline (TH)/ CTS/β-cyclodextrin(β-CD) microspheres by spray-drying method. Previous studies for pulmonary delivery also showed that β-CDs could markedly improve the poor solubility of cyclosporine A [7] , and the pharmaceutical and biopharmaceutical properties of drugs without lowering their pulmonary deposition [8] .…”
Section: Introductionmentioning
confidence: 97%
“…Cyclodextrins offer an interesting and promising approach for solubilisation, which are ring-forming oligosaccharides consisting of six, seven or eight glucose molecules and which have a sweet taste on inhalation [44,45]. The α-, β-and γ-cyclodextrins differ with respect to their molecular weight (927.9 -1297) and size of the cavity defined by the inner (0.57 -95 nm) and outer (1.37 -1.69 nm) diameter.…”
Section: Novel Optimised Formulations For Nebulisationmentioning
confidence: 99%